The international financial crisis and its impact on Peru - Chávez Álvarez, Jorge (2012)
As you know, the financial crisis broke out in September 2008 with the bankruptcy of the largest investment bank in the United States, Lehman Brothers. Previously, the U.S. government had already come to the rescue of two giant companies dedicated to the mortgage business: Fannie Mac and Freddie Mac, holders of 50% of the U.S. mortgage pie; an operation that involved pawning a lot of U.S. taxpayers' money, and which has been paid for with the issuance of U.S. Federal Reserve bills.